Rock Art Studies - International Conference on Rock Art (2012 : New Delhi, India); Malla, B. L; Indira Gandhi National Centre for the Arts (New Delhi, India) (New Delhi : Aryan Books Internationl : Indira Gandhi National Centre for the Arts, 2014)
Special lectures delivered at the International Conference on Rock Art, held at New Delhi during 6th December 2012 to 23rd January 2013
volume 1. Concept, methodology, context, documentation and conservation. -- volume 2. Interpretation through multidisciplinary approaches.
Includes bibliographical references.
Keywords: Rock paintings in art -- Congresses; Rock paintings -- Congresses; Petroglyphs -- Congresses; Art, Prehistoric -- Congresses